'An Awkward Part to Play': Byron, Gaming, and the Perils of Courtship. Issue 2 (1st December 2022) - McDayter, Ghislaine
Abstract : Byron, notoriously, liked to play games. Whether actual card games, such as the Regency staple of Speculation so beloved of Jane Austen, or the more performative realm of 'playing' a role for the benefit of the ton, he frequently invokes in his writing the excitement intrinsic to risking high stakes and paying the price of a personal gamble. Such overpowering sensations, he insists, remind us that we are alive. What the following will argue is that while the poet's keen interest in 'play' often becomes a metaphor for the vagaries and dangers of Regency courtship practices, Byron's exploration of the language and habits of gamblers leads us to a deeper understanding of the poet's views on gender roles and sexuality, harnessing the power of sexuality to the crucial experience of human risk in both gaming and love play.